Spiritual and Ecological Relations: An Ecotheological Analysis of the Local Wisdom of the Sembalun Community in Environmental Conservation - Diki Wahyudi (International Journal of Sociology of Religion, 2026)
This study examines the relationship between spiritual dimensions and ecological practices within the local wisdom of the Sembalun community in East Lombok Regency as a community-based environmental conservation mechanism. Employing an ecotheological framework, the research explores how sacred cosmology, traditional rituals, and social governance function as a holistic and sustainable system of conservation. A qualitative method with an ecological ethnography design is applied through participant observation, in-depth interviews with customary leaders, ritual practitioners, farmers, and village administrators, as well as documentation studies of customary texts and village regulations. The findings indicate that the Sembalun community perceives nature as a sacred living entity, manifested in the concept of Gumi Sasak, ecological spatial zoning (protected forests, sacred areas, and productive lands), and rituals such as Mepanten, Environmental Nyepi, and periods of restriction (Sasi). These practices empirically contribute to forest cover preservation, water source stability, and agroecosystem resilience. Ecotheological analysis reveals that the integration of spirituality and environmental ethics within local wisdom offers a relational model that challenges modern anthropocentric paradigms. This study recommends institutional recognition of local knowledge systems in environmental governance policies, as well as strengthening intergenerational knowledge transmission amid the pressures of tourism and climate change.